Prostaglandin synthetase activity from human rheumatoid synovial microsomes. Effect of 'aspirin-like' drug therapy. Issue 4 (August 1976) - Crook, D; Collins, A J; Bacon, P A; Chan, R
Abstract : Using a radiometric technique, prostaglandin synthetase activity was measured in vitro in the microsomal fraction of 19 synovial tissues taken from 17 rheumatoid arthritis patients. The enzyme was inhibited in vitro by low concentrations of several 'aspirin-like' drugs, though paracetamol and salicylic acid were virtually inactive. While the synthetase preparations from patients receiving indomethacin, ibuprofen, or naproxen therapy exhibited considerable activity in vitro, we were unable to show any activity in preparations from patients taking aspirin, even in low doses. These findings suggest that in vivo aspirin may be unique in being an irreversible inhibitor of the enzyme, compared with other 'aspirin-like' drugs.